1981
DOI: 10.1126/science.7195069
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Withdrawal from Opiates Interferes with Hatching of Otherwise Viable Chick Fetuses

Abstract: Fetal chicks were made opiate-dependent by injections of N-desmethyl-1-alpha-acetylmethadol into the chorioallantois on day 3 of embryogenesis. The injections had no effect on subsequent hatchability; however, spontaneous fetal motility was significantly depressed. Injection of naloxone caused a significant increase in the motility of the opiate-exposed fetuses but had no effect on control fetuses. That naloxone's effect was an expression of opiate withdrawal and not due to antagonism of depressed motility is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 18 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Consequently, disruption of the natural course of cellular events occurring during this early period may lead to later functional disorders. The similarity of agonist-antagonist effects on adenylate cyclase during early embryonic development may be of functional signifiLcance in partially explaining the effects of prenatal opiate withdrawal reported in the rat (11) and the chick (12). These investigators were able to show that opiate withdrawal in utero increased neonatal morbidity in the rat and that withdrawal from opiates interfered with hatching in otherwise viable chicken fetuses.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Consequently, disruption of the natural course of cellular events occurring during this early period may lead to later functional disorders. The similarity of agonist-antagonist effects on adenylate cyclase during early embryonic development may be of functional signifiLcance in partially explaining the effects of prenatal opiate withdrawal reported in the rat (11) and the chick (12). These investigators were able to show that opiate withdrawal in utero increased neonatal morbidity in the rat and that withdrawal from opiates interfered with hatching in otherwise viable chicken fetuses.…”
Section: Discussionmentioning
confidence: 94%
“…7 and 8). In addition, the interaction between the opiate antagonist naloxone and the adenylate cyclase system is important because opiate antagonists (naltrexone) are currently being used in the treatment ofopiate addiction (9, 10) and a toxic effect on the embryo has been suggested (11,12). These investigators showed, in both the chicken and the rat, that administration of naloxone to morphine-dependent embryos increased their morbidity as compared with low doses of morphine alone.…”
mentioning
confidence: 99%
“…Opiate withdrawal is not recommended during pregnancy unless the mother refuses opiate maintenance therapy due to increased likelihood of relapse (ACOG Committee, 2012). Animal studies have demonstrated in utero withdrawal to increase fetal activity and perinatal mortality (Kirby and Holtzmann, 1982;Kuwahara and Sparber, 1981;Lichtblau and Sparber, 1981).…”
Section: Opiate Maintenance Therapiesmentioning
confidence: 99%
“…It is a general assumption that perinatal morbidity is caused by the development of narcotic dependence in the fetus as a direct result of placental transport of the drug. However, these difficulties may have their origin in utero as the result of the fetus experiencing withdrawal during gestation (Kuwahara & Sparber, 1981; Lichtblau & Sparber, 1981). At birth, the newborn infant continues to experience withdrawal due to the absence of the drug.…”
mentioning
confidence: 99%